2011
DOI: 10.1111/j.1365-2761.2011.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of infectious gill disease in marine salmonid fish

Abstract: Infectious gill diseases of marine salmonid fish present a significant challenge in salmon-farming regions. Infectious syndromes or disease conditions affecting marine-farmed salmonids include amoebic gill disease (AGD), proliferative gill inflammation (PGI) and tenacibaculosis. Pathogens involved include parasites, such as Neoparamoeba perurans, bacteria, such as Piscichlamydia salmonis and Tenacibaculum maritimum, and viruses, such as the Atlantic salmon paramyxovirus (ASPV). The present level of understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
144
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 95 publications
8
144
0
6
Order By: Relevance
“…This method is particularly suitable on Atlantic salmon farms that are constantly affected by the disease, allowing operators to become familiar with the gross presentation of lesions. However, the gross gill score can be difficult to interpret when non-AGD pathologies, such as proliferative gill disease or gill necrosis are present (Steinum et al, 2010;Mitchell and Rodger, 2011). It is also reported that the gross gill scoring method is less applicable for other fish species affected by AGD, such as lumpfish (Cyclopterus lumpus) which are used as cleaner fish in Atlantic salmon cages (Haugland et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…This method is particularly suitable on Atlantic salmon farms that are constantly affected by the disease, allowing operators to become familiar with the gross presentation of lesions. However, the gross gill score can be difficult to interpret when non-AGD pathologies, such as proliferative gill disease or gill necrosis are present (Steinum et al, 2010;Mitchell and Rodger, 2011). It is also reported that the gross gill scoring method is less applicable for other fish species affected by AGD, such as lumpfish (Cyclopterus lumpus) which are used as cleaner fish in Atlantic salmon cages (Haugland et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…High salinity (> 32 ppt) and periods of low rainfall strongly correlate with AGD outbreaks (Munday et al 2001, Mitchell & Rodger 2011, Nowak 2012. Further, efficacy of freshwater baths in assuaging AGD infections in salmon (Nowak 2012), along with the crenation, ceased growth and death of N. pemaquidensis cells at low salinities (Lee et al 2006), infer that N. perurans are susceptible to salinity changes.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical and histologic signs of diseased fish were similar to those of AGD in other species reported previously. 7,10 In PCR assays, all samples (3 fish) showed specific N. perurans 636-bp fragments. When these PCR products of N. perurans-positive samples were sequenced, nucleotide sequences of these isolates from black seabream (BSBGoH15) and rock bream (RBGoH15) showed 98.3% sequence identities to each other.…”
Section: Research-article2017mentioning
confidence: 99%
“…Scophthalmus maximus), European seabass (Dicentrarchus labrax), sharpsnout seabream (Diplodus puntazzo), ballan wrasse (Labrus bergylta), and ayu (Plecoglossus altivelis) in Spain, South Africa, the Mediterranean, Norway, and Japan. [1][2][3][7][8][9] Thus, AGD threatens the marine farming industry in many countries.The clinical signs of AGD include multiple white-to-gray patches on swollen gills, with excess mucus surrounding gill arches. 7 The main histologic feature of AGD is prominent epithelial hyperplasia in the gills, resulting in complete lamellar fusion.…”
mentioning
confidence: 99%